LESSON STUDY APPROACH IN LEARNING RESPIRATORY SYSTEM TO IMPROVE CRITICAL THINKING SKILLS - Anggraini, Pradita Putri; Keliat, Natalia Rosa; Tapilouw, Marisa Christina (Universitas Tanjungpura, 2025)
The objectives of this study were 1) to improve student's critical thinking skills through Problem Based Learning (PBL) with a Lesson Study approach on respiratory system material; 2) to analyze students' critical thinking skills in studying the respiratory system; 3) to determine the differences in the effect of the PBL-LS and PBL learning models on critical thinking skills in the material of the respiratory system. This study used a quasi-experimental design. The subjects in this study were XI MIPA 1 and XI MIPA 2 grade SMA Negeri 1 Salatiga. This research was conducted in the even semester of the 2022/2023 Academic Year from September 2023 to May 2022. The data analysis technique used is quantitative descriptive analysis. Based on the research results, it is known that there is an influence of the PBL-LS learning model on critical thinking skills (p-value 0.05) with an N-Gain of 0.5 (moderate). The results of the analysis of each indicator of critical thinking skills showed from that the lowest indicator to the highest indicator of critical thinking skills was found from the inference (65,8); reason (69,4); clarity (69,8); focus (72,8); overview (75,0); situation (79,7). In addition, it was also found that there was a difference in the effect of the PBL-LS and PBL learning models on critical thinking skills (p-value 0.05).